Clinical phenotypes and outcomes of precapillary pulmonary hypertension of sickle cell disease. Issue 6 (5th December 2019) - Savale, Laurent; Habibi, Anoosha; Lionnet, François; Maitre, Bernard; Cottin, Vincent; Jais, Xavier; Chaouat, Ari; Artaud-Macari, Elise; Canuet, Matthieu; Prevot, Grégoire; Chantalat-Auger, Christelle; Montani, David; et al.
Rationale: Precapillary pulmonary hypertension (PH) is a devastating complication of sickle cell disease (SCD). Little is known about the influence of the SCD genotype on PH characteristics. Objectives: To describe clinical phenotypes and outcomes of precapillary PH due to SCD according to disease genotype. Methods: A nationwide multicentre retrospective study including all patients with SCD-related precapillary PH from the French PH Registry was conducted. Clinical characteristics and outcomes according to SCD genotype were analysed. Results: 58 consecutive SCD patients with precapillary PH were identified, of whom 41 had homozygous for haemoglobin S (SS) SCD, three had S-β0 thalassaemia (S-β0 thal) and 14 had haemoglobin SC disease (SC). Compared to SC patients, SS/S-β0 thal patients were characterised by lower 6-min walk distance (p=0.01) and lower pulmonary vascular resistance (p=0.04). Mismatched segmental perfusion defects on lung scintigraphy were detected in 85% of SC patients and 9% of SS/S-β0 thal patients, respectively, and 50% of SS/S-β0 thal patients had heterogeneous lung perfusion without segmental defects. After PH diagnosis, 31 patients (53%) received medical therapies approved for pulmonary arterial hypertension, and chronic red blood cell exchange was initiated in 23 patients (40%). Four patients were managed for chronic thromboembolic PH by pulmonary endarterectomy (n=1) or balloon pulmonary angioplasty (n=3). Overall survival was 91%, 80% and 60% at 1, 3 and 5 years, respectively, without influence of genotype on prognosis. Conclusions: Patients with precapillary PH related to SCD have a poor prognosis. Thrombotic lesions appear as a major component of PH related to SCD, more frequently in SC patients. Clinical phenotype of precapillary pulmonary hypertension of sickle cell disease is influenced by the genotype. Thrombotic lesions appear as a major component of PH related to SCD, more frequently in SC patients. http://bit.ly/32b2nEx